Kara śmierci w przekazie Talmudu Babilońskiego - Łabuda, Piotr (Analecta Cracoviensia, 2012)
When reading the Babylonian Talmud it has to be noted that it gives a fragmentary account of the capital punishment. However, the Talmud indicates who, for what and in what way should be condemned. The Talmud’s account of Jesus’ death is even shorter. It is not only pure fiction but is also a result of the authors’ deliberate action. The description of b. Sanh 43a, in a particular way, shows the clear goal - to discredit Jesus. What is written about Jesus’ death in the Talmud can be explained as personal and peculiar Jewish interpretation based on clearly defined intentions.